MENAKAR LEMBAGA PENDIDIKAN KELUARGA DALAM BINGKAI TIGA TAHAP PERKEMBANGAN C.A. VAN PEURSEN - Nadlifah Nadlifah (Jurnal Pendidikan Agama Islam, 2013)
Family education institution is an educational institution that is first and foremost for the children in building the foundations of moral life, social and religious. When educational institutions intersect with science and technology, it appears the two polarization family, namely the nuclear family and the extended family. The presence of concomitant effects can impact on alienation of science and technology and inconsistency in the status of the family. According to the three stages of development C.A. glasses Van Peursen, extended family in the category of mythic stage, while the nuclear family in the category of ontological and functional stages.